2021
DOI: 10.1101/2021.11.01.466782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Btbd11 is an inhibitory interneuron specific synaptic scaffolding protein that supports excitatory synapse structure and function

Abstract: SUMMARYSynapses in the brain exhibit cell-type-specific differences in basal synaptic transmission and plasticity. Here, we evaluated cell-type-specific differences in the composition of glutamatergic synapses, identifying Btbd11, as an inhibitory interneuron-specific synapse-enriched protein. Btbd11 is highly conserved across species and binds to core postsynaptic proteins including Psd-95. Intriguingly, we show that Btbd11 can undergo liquid-liquid phase separation when expressed with Psd-95, supporting the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Our analysis revealed major differences in the PSD between glutamatergic and GABAergic neuronal subtypes in both the developing and adult neocortex. This is consistent with previous studies showing that the composition of the PSD is diverse among neuronal subtypes ( 4648 ). One limitation of this inference is that single-cell RNA-sequencing does not include RNAs in dendrites that could contribute to the PSD through local translation.…”
Section: Discussionsupporting
confidence: 94%
“…Our analysis revealed major differences in the PSD between glutamatergic and GABAergic neuronal subtypes in both the developing and adult neocortex. This is consistent with previous studies showing that the composition of the PSD is diverse among neuronal subtypes ( 4648 ). One limitation of this inference is that single-cell RNA-sequencing does not include RNAs in dendrites that could contribute to the PSD through local translation.…”
Section: Discussionsupporting
confidence: 94%
“…UMAP revealed six major clusters attributed to canonical cell lineage‐specific markers (Figures 2b,c). These were astrocytes (Ast; e.g., SLC1A2 and GFAP ) (Lake et al, 2017; Zhong et al, 2018), endothelial cells (End; e.g., IGFBP7 and FLT1 ) (Darmanis et al, 2015; Fan et al, 2018), excitatory neurons (Ex; e.g., SATB2 and NEFM ) (Lake et al, 2016; Rowell et al, 2010), inhibitory neurons (In; e.g., GAD2 and BTBD11 ) (Bygrave et al, 2021; Shi et al, 2021), oligodendrocytes (Oli; e.g., MBP , OPALIN , MOG , MOBP , and ENPP2 ; Darmanis et al, 2015; Hodge et al, 2019; Mizrak et al, 2019; Welch et al, 2019), and oligodendrocyte precursor cells (Opc; e.g., VCAN and TNR ) (Lake et al, 2017; Mizrak et al, 2019). The number of unique molecular identifiers (UMIs) and genes in each cell type showed that this data set passed stringent high‐quality filtering and was suitable for snRNA‐seq analysis (Figure S1b).…”
Section: Resultsmentioning
confidence: 99%
“…Animal models 51,52 and controlled trials 53,54 have demonstrated that agonists to GABA receptors inhibit the cough reflex; specifically, baclofen has been shown to supress ACEI-induced cough 55 . Further, INHBC is expressed in the nervous system and is known to suppress inflammatory pain responses 42 and current evidence demonstrates the role of BTBD11 in regulating glutamatergic synapse function 43 . Also, combined with additional support from previous genomic studies 11 , in vitro and in vivo studies 56 of KCNIP4 activity provide evidence for the role of neuronal potassium channels in smooth muscle reactivity and cough reflex modulation, and also suggest that they are a promising target for antitussive therapies 57 .…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the transforming growth factor (TGF)-beta protein superfamily, INHBC also has a role in SMAD protein signal transduction, and its expression in sensory neurons is required to suppress inflammatory pain 42 . Similarly, BTB Domain Containing 11 (BTBD11) is involved in SMAD protein signal transduction, and has been identified as an inhibitory interneuron-specific protein localised to the brain cortex and hippocampus and interacts with glutamatergic synapses 43 . Vacuolar ATPase assembly factor VMA21 (VMA21) is a chaperone for the assembly of lysosomal vascular ATPase 31 , and XRCC6 Binding Protein 1 (XRCC6BP1) is a metallopeptidase also involved in ATP synthase assembly, as well as DNA repair 31 .…”
Section: Identification Of Putative Causal Variants and Genesmentioning
confidence: 99%